Paradoks Hukum Rekayasa Sosial Pig Butchering Scam Dalam Investasi Digital Aset Kripto - Ashibly, Ashibly (Jurnal Hukum IUS QUIA IUSTUM, 2025)
The phenomenon of social engineering in the world of digital crypto asset investment has become an increasingly pressing concern in Indonesia, where investors are often trapped in fraudulent schemes that claim to offer high opportunities with low risk. The Pig Butchering Scam is one form of fraud that is currently occurring. The purpose of this study is to analyze the pig butchering scheme through the function of law as a social engineering tool designed to form policies to create new conditions. The research method used is Normative Legal Research, using a conceptual approach. Data sources include primary legal materials consisting of laws and regulations related to the research and secondary legal materials consisting of law books and so on. Data collection was carried out through a study of legal norms, legal regulations, and the legal system in general, as well as qualitative data analysis techniques, with a focus on interpretation. The research findings indicate that the legal paradox of the pig butchering scam social engineering in digital crypto asset investment in Indonesia, when faced with cross-border legal regulations, is not yet supported by a strong international framework. Mutual legal assistance (MLA) can be a solution, but in practice, it also has weaknesses, such as Indonesia's limitations in bilateral agreements. In conclusion, the government is obliged to cooperate and establish regulations bilaterally and multilaterally to protect the interests of its citizens from cybercrime. With international regulations, participating countries can align uniform legal standards and provide global protection, particularly in the case of crypto-asset investment crimes.